Increased prevalence of stunting in Pakistan: A comparative analysis of National Nutrition Surveys - Khalid, Nauman (Journal of the Pakistan Medical Association, 2025)
Stunting continues to be a major public health concern worldwide and can have lifelong consequences for the affected individuals in terms of both physical and cognitive development. Among South Asian countries, Pakistan continues to experience consistently high rates of stunting, owing to a wide range of factors. National nutrition surveys and reports by various international organisations indicate that a significant reduction has not been observed in stunting rates over the last 3-4 decades and that the progress for mitigating the problem remains inadequate. The current report was planned to analyse nationally representative surveys done in 2001-02, 2011 and 2018 to ascertain the major determinants of stunting, their complex interplay, and the contribution of these determinants to the increased prevalence of stunting in Pakistan. Key Words: Stunting, Malnutrition, Pakistan, National nutritional survey.